Specific Prenylation of Tomato Rab Proteins by Geranylgeranyl Type-II Transferase Requires a Conserved Cysteine-Cysteine Motif. - Yalovsky, S. (1996)
Posttranslational isoprenylation of some small GTP-binding proteins is required for their biological activity. Rab geranylgeranyl transferase (Rab GGTase) uses geranylgeranyl pyrophosphate to modify Rab proteins, its only known substrates. Geranylgeranylation of Rabs is believed to promote their association with target membranes and interaction with other proteins. Plants, like other eukaryotes, contain Rab-like proteins that are associated with intracellular membranes. However, to our knowledge, the geranylgeranylation of Rab proteins has not yet been characterized from any plant source. This report presents an activity assay that allows the characterization of prenylation of Rab-like proteins in vitro, by protein extracts prepared from plants. Tomato Rab1 proteins and mammalian Rab1a were modified by geranylgeranyl pyrophosphate but not by farnesyl pyrophosphate. This modification required a conserved cysteine-cysteine motif. A mutant form lacking the cysteine-cysteine motif could not be modified, but inhibited the geranylgeranylation of its wild-type homolog. The tomato Rab proteins were modified in vitro by protein extract prepared from yeast, but failed to become modified when the protein extract was prepared from a yeast strain containing a mutant allele for the [alpha] subunit of yeast Rab GGTase (bet4 ts). These results demonstrate that plant cells, like other eukaryotes, contain Rab GGTase-like activity.